The Bohemo‐Iberian regional chronostratigraphical scale for the Ordovician System and palaeontological correlations within South Gondwana. (25th November 2016) - Gutiérrez‐Marco, Juan Carlos; Sá, Artur A.; García‐Bellido, Diego C.; Rábano, Isabel
Abstract: The Bohemo‐Iberian regional scale for South Gondwana, involving the 'Mediterranean Province', comprises five regional stages (Arenigian, Oretanian, Dobrotivian, Berounian and Kralodvorian) plus the global Tremadocian and Hirnantian. The predominance of shallow‐water taxa in those high‐latitude faunas imposes serious difficulties for correlating the regional succession with the formal global chronostratigraphy because of the almost total absence of the key graptolites and conodonts defining the base of the standard series, stages and stage slices. Instead, the abundant benthic faunas (trilobites, brachiopods, molluscs, echinoderms) of South Gondwanan origin largely dominated in the area from the middle Darriwilian to the late Katian. The poleward faunal migration of originally Avalonian, Baltic, Laurentian and even Asiatic taxa during the Boda Event of global warming progressively ends with the endemicity in the region, where the ensuing benthic assemblages were severely affected by the Hirnantian glaciation. The regional scale significantly improves the precision of correlations between Ordovician strata from SW and central Europe, North Africa and a large part of the Middle East. An updated record of palaeontological data from areas where Mediterranean faunas remain practically unknown, or are still poorly investigated, is also included. Palaeobiogeographical relationships based on the distribution of faunas across South Gondwana are suggested as an improvement for positioning many territories in modern palaeogeographical reconstructions and offer a constructive approach to problems related to the pre‐Variscan and pre‐Alpine orogenic puzzles.